Penerapan Asuhan Keperawatan Kepada Pasien Diabetes Melitus Di Ruang Dewasa RSUD Maren Hi. Noho Renuat Kota Tual - Siti Rochmaedah; Yerry Soumokil; Kiky Rizkyah Serang (Jurnal Medika Nusantara, 2023)
Diabetes mellitus is a state of chronic hyperglycemia accompanied by metabolic disorders due to hormonal disturbances, which causes various chronic complications in the eyes, kidneys, nerves and blood vessels accompanied by lesions on the basement membrane in electron microscopy examination. Gangrene is a process or condition characterized by the presence of dead tissue or necrosis, but microbiologically it is a process of necrosis caused by infection. Wounds can be interpreted as disruption or damage to the integrity and function of tissues in the body. Someone who suffers from an injury will feel imperfection which in turn tends to experience physical and emotional disorders. This means, someone who has an injury will experience health problems that can have an impact on the quality of his life.